2019
DOI: 10.1093/eurheartj/ehz594
|View full text |Cite|
|
Sign up to set email alerts
|

Paclitaxel-coated balloon angioplasty vs. drug-eluting stenting for the treatment of coronary in-stent restenosis: a comprehensive, collaborative, individual patient data meta-analysis of 10 randomized clinical trials (DAEDALUS study)

Abstract: Aims Consensus is lacking regarding the best treatment for coronary in-stent restenosis (ISR). The two most effective treatments are angioplasty with paclitaxel-coated balloon (PCB) and repeat stenting with drug-eluting stent (DES) but individual trials were not statistically powered for clinical endpoints, results were heterogeneous, and evidence about comparative efficacy and safety in relevant subsets was limited. Methods and results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(120 citation statements)
references
References 39 publications
(23 reference statements)
3
107
0
2
Order By: Relevance
“…The recent DAEDALUS study in patients treated with DCB or DES for in-stent re-stenosis showed that there was no significant difference in late mortality associated with DCB. This conclusion is limited however, by the fact that followup was limited to 3 years and thus might have missed a true late effect [19]. In addition, it is difficult to draw definitive conclusions from that study for late mortality relating to paclitaxel, as this was a subgroup analysis and the patient groups were heterogeneous given the previous stent implantations including bare metal stents and paclitaxel DES.…”
Section: Discussionmentioning
confidence: 99%
“…The recent DAEDALUS study in patients treated with DCB or DES for in-stent re-stenosis showed that there was no significant difference in late mortality associated with DCB. This conclusion is limited however, by the fact that followup was limited to 3 years and thus might have missed a true late effect [19]. In addition, it is difficult to draw definitive conclusions from that study for late mortality relating to paclitaxel, as this was a subgroup analysis and the patient groups were heterogeneous given the previous stent implantations including bare metal stents and paclitaxel DES.…”
Section: Discussionmentioning
confidence: 99%
“…Calcified lesion modification with this device, as measured by optical coherence tomography, was favorably rated in previous observational studies [ 18 ]. Given the fact that there is no class effect for DCB devices [ 4 ] the iopromide–paclitaxel-coated DCB was used (SeQuent ® Please NEO, B.Braun Melsungen AG). As compared to the predecessor device (SeQuent ® Please, B.Braun Melsungen AG), a hydrophilic coating of the distal shaft was introduced for enhanced lesion crossability.…”
Section: Methodsmentioning
confidence: 99%
“…Lumen gain prior to DCB angioplasty may be of paramount importance in the absence of stent or scaffold implantations due to elastic recoil and/or dissections. However, pivotal studies for DCB angioplasty were primarily conducted to treat in-stent restenotic (ISR) lesions with documented high restenosis [ 4 ]. Numerous studies provided sufficient evidence for a renewed class I recommendation by the European Society of Cardiology for in-stent restenosis with an evidence level A [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of restenosis, the DAEDALUS study, a patient-level meta-analysis including 10 RCT, showed that treatment of in-stent restenosis (ISR) with DCB was associated with a higher risk of TLR at 3 years, with no differences in the safety outcome (death, MI, or target lesion thrombosis). 60 A sub-analysis of this study, comparing BMS-ISR and DES-ISR, demonstrated that both treatment strategies (DCB and new DES implantation) were similarly effective and safe in patients with BMS-ISR. However, in patients with DES-ISR, treatment with DCB was associated with a higher rate of TLR at 3 years and non-significant differences in safety outcomes.…”
Section: Lesion Subsetsmentioning
confidence: 73%